O Neobarroco na poesia de Aníbal Beça - Ferreira, Klebson Maia (2014)
Aníbal Beça was poet, translator, composer, playwright and journalist. He is began his literary career in the 60s, in the gloomy context of dictatorship and after the unrest and rebellion that characterized the Clube da Madrugada, a landmark of modernist renovation in Amazonas, appeared under the influence of the generation of 45 and spiritualistic tendency, represented by Jorge de Lima and Murilo Mendes. But as pointed Tenorio Telles ends up identifying with the more experimental side of Brazilian literature. His formal survey reveals, beyond the careful processes of elaboration, a concern of art destinations in Latin America, which explains its active position. From this it is possible to understand the role of the neo-baroque in his poetry. How Irlemar Chiampi made with respect to Lezama Lima literature, Severo Sarduy, among other important Latin American authors, in this paper we seek to understand what a time it deepens the question of modernity and art and how it engenders the confluence of European culture and indigenous cultures subjugated here, resulting in civilizations for which the Enlightenment project was left unfinished or impossible. This study investigates the neo-baroque, defined as post-utopian and analogy of contemporary art forms with the seventeenth-century representation, pointing out how this aesthetic question presents itself in the art of Amazonian poet, markedly influenced by Ezra Pound, for which the poet is primarily a seismograph of his time. Finally, we elaborate an anthology under the aforementioned aesthetic ballast. Keywords: baroque, allegory, concrete poetry, neo-baroque poetry.